The Effect of Organizational Justice on Job Satisfaction Mediated by Organizational Commitment - Sheenia Meilliana; Yanuar Yanuar (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to determine the impact of organizational justice on organizational commitment mediated job satisfaction. This research was conducted at XYZ Company by distributing questionnaires via google form with 60 respondents. This study uses the SEM (Structural Equation Modeling) method with SmartPLS software to test the validity and reliability of the analysis The results show that organizational justice has no effect on job satisfaction, organizational justice has a positive and significant impact on organizational commitment, organizational commitment has a positive and significant impact on job satisfaction, and organizational justice has a positive and significant impact on organizational commitment. In addition, the firm will get benefit by how organizational can improve as well as increase job satisfaction. In order to achieve organization goals, company can understand the employee’s job satisfaction.